Evaluating Gender Perspectives in Energy Efficiency Programs: A Case Study of the Municipality of Brvenica - Alili Merita Zulfiu; Tankosikj Katerina Koneska; Memeti Memet (SEEU Review)
This study analysis the Energy Efficiency Program of the Municipality of Brvenica, examining its budgetary aspects through the lens of gender-responsive measures. The program, spanning 2022-2024, allocates funds for diverse energy efficiency projects but falls short in addressing residential households and lacks ambitious renewable energy measures. The absence of gender-disaggregated data underscores a gap in understanding the impact on women and men. Recommendations urge aligning the program with gender equality policies, expanding goals, and consulting the Commission for Equal Opportunities. The study advocates for gender-sensitive measures, citizen involvement, and increased funds for household energy efficiency. Budgetary analysis reveals a disconnection between the program and the municipal budget, emphasizing the need for better integration. Challenges include the absence of gender-specific data and limited consultation during program development. Recommendations stress enhanced budget transparency, increased financial allocations for gender-responsive initiatives, and collaboration for ecological heating awareness. The study underscores the imperative of comprehensive gender integration in energy policies for equitable outcomes and effective mitigation of energy poverty.